PELATIHAN PENGOLAHAN LIMBAH TERNAK MENJADI KOMPOS DAN POC UNTUK PEMBERDAYAAN PETERNAK DI KTT DOKAM MAKMUR, SUKOHARJO - Yuli Yanti; Madda Yanuarifky; Mifta Adi Saputro; Mochamat Chisbul Fajar; Mohammad Puguh Setyawan; Muhammad Faqih Nur Fathin; Saras Nahya Nurhaliza Nugroho; Vika Malinda; Devana Novitha Fitriyana; Mahsa Asaria Sahda; Wari Pawestri; Dewanto Harjunowibowo (Universitas Mataram, 2026)
The sheep and goat farming sector plays a vital role in providing animal protein, but sheep and goat farming is still dominated by traditional farmers who have not yet implemented Good Management Practices (GMP). One application of GMP is waste management to prevent environmental pollution. The Dokam Makmur livestock group in Sukoharjo still maintains its livestock in a very simple manner and is not yet familiar with technology, especially in waste processing. This community service aims to increase the capacity of the Dokam Makmur Livestock Farmers Group (KTT) farmers in Kedungjambal Village, Sukoharjo, in managing livestock waste into economically valuable products through empowerment in the form of counseling and training. The method used is a participatory approach through material delivery, technical demonstrations, interactive discussions, and direct practice in making solid (compost) and liquid organic fertilizer (POC) using EM4 and molasses fermentation. Data before and after the training were collected using a questionnaire. The implementation stages of this activity began with a presentation of material on goat and sheep health, followed by a presentation of material on processing manure and urine into quality fertilizer. The results of the activity showed a significant increase in the knowledge and skills of livestock farmers, with the highest achievements in the aspects of making POC from urine (85.8%) and mastitis detection techniques (71.4%). The community response was very positive, marked by high participation in discussions (85.7%) and interest in entrepreneurship after the grant of compost production equipment. The contribution of this community service is not only to reducing waste and environmental pollution, but also to empowering the economy of livestock farmers through sustainable waste processing innovations. The conclusion of this community service activity is that the community service activity at the KTT Dokam Makmur, Sukoharjo, successfully increased the capacity of livestock farmers in managing livestock waste into solid and liquid organic fertilizer through EM4 and molasses fermentation.